Billeder i brug: Lidt om andagt, kult og sjælestiftelser i senmiddelalderens Odense - Johannsen, Birgitte Bøggild (Hikuin, 1999)
Images in Use. Some Remarks on Private Devotion, Cult and Frankalmoins in Late Medieval Odense. By Birgitte Bøggild Johannsen During the last decade the corpus of Danmarks Kirker, edited by the Danish National Museum have published the descriptions of the churches and monasteries in medieval Odense. These descriptions form the starting point of a discussion on the use and function of images in the Late Medieval church, in particular related to the furnishing of the chancels of the monastery churches of the order of the Knights Hospitallers of St. John of Jerusalem (St. Hans’ Church) and of the Greyfriars (Gråbrødre Church). The chancel in St. Hans resulted from af radical rebuilding of the monastery church, finished c. 1475 and to a large extent financed by donations from the nobility of Funen. After completion the chancel was embellished with wall paintings, an altar piece – a winged retable, displaying the image of the Rosary Madonna between St. Michael and St. John, and a rood screen between the chancel and the nave, crowned by a huge crucifix, the only existing item of the Late Medieval furniture. Lost is also the church treasure of the vasa sacra and textiles, a.o. a reliquary in the shape of the head of St. John the Baptist. An impression of the liturgical practice and the use of images in the church on particular feast days and in connexion with memorial services, relevant to single members of the community can be deducted from two important sources, the foundation document from 1468 of a Requiem service on behalf of the Counsellor of State, Eggert Frille, later buried in the chancel in front of the high altar, and the Royal account book of Queen Christine, wife of King Hans, covering the period c. 1504-21. The imagery of the chancel in St. Hans’ Church is compared with the even more exuberant decoration of the chancel in Greyfriars Church, furnished during the first decades of the 16th century by Queen Christine in order to serve as a Royal mausoleum.